1981
DOI: 10.1159/000149249
|View full text |Cite
|
Sign up to set email alerts
|

Production of R-Type Virus-Like Particles in Hamster Cells

Abstract: The production and release of R-type virus-like particles (VLP) was studied in several Syrian hamster cell lines. Most but not all hamster cell lines contain detectable levels of R-type VLP. However, only BHK-21 clone F (CF) cells would release the VLP into culture fluids. Treatment with dexamethasone enhanced to a limited extent the production and release of VLP from BHK-21 CF cells. Actinomycin D inhibited the production and release of R-type VLP in hamster cells, suggesting that some transcription from DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The description of putative extracellular IRP particles found in some reports [2] could be explain by the fact that SH cells possess endogeneous retroviruses [ 13], with a morphology evoking that of IRP.…”
Section: Discussionmentioning
confidence: 99%
“…The description of putative extracellular IRP particles found in some reports [2] could be explain by the fact that SH cells possess endogeneous retroviruses [ 13], with a morphology evoking that of IRP.…”
Section: Discussionmentioning
confidence: 99%
“…The lineage and safety of mammalian-derived cell lines are important for regulatory filings in support of biotherapeutic manufacturing methods for clinical trials. BHK cells have been shown to generate (Albu and Holmes, 1973) and release (Bergmann and Wolff, 1981) endogenously produced viruslike particles (VLPs); however, the BHK cell line has been used both in a Huntington's disease phase 1 clinical trial to deliver ciliary neurotrophic factor (CNTF) (Bloch et al, 2004) and for the manufacture of recombinant factor VIII to treat hemophilia A. The latter is a U.S. Food and Drug Administration (FDA)-licensed, commercial process (Boedeker, 2001), validating the use of BHK cell-based manufacturing as a viable method for the production of human therapeutics.…”
Section: Bhk Cell Line and Suspension Growthmentioning
confidence: 99%
“…Up to now in different rodent tumours and transformed cell lines these endogenous retrovirus-related sequences could be classified as C-type, intracisternal A~particles (lAP), virus-like (VL-30) and mouse mammary tumour virus (MMTV) families [5,7,8,11]. As for the Rtype VLP, they are considered as EV and classified as intracisternat R-type by Bergmann and Wolff [1] and Lasneret et al [9], who found them in activated by 5-iododeoxyuridine or demethylating drug hamster cell lines. In their experiments these particles were sometimes accompanied by intracisternal A-type, intracytoplasmic A-type, intramitochondrial A-type and type C VLP.…”
mentioning
confidence: 99%